1989
DOI: 10.1029/jd094id12p14629
|View full text |Cite
|
Sign up to set email alerts
|

A review of the photochemistry of selected nightglow emissions from the mesopause

Abstract: The substantial research activity of recent years on the photochemistry of the hydrogen‐oxygen family has improved our understanding of the production of nightglow emissions in the mesopause region of the atmosphere between 80 and 100 km; this work is reviewed with specific attention paid to the emissions of OH, the 557.7‐nm emission of O, and the atmospheric bands of O2(b 1Sg). These emissions are closely related to the O atom concentration profile and would provide a wealth of useful photochemical data in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 105 publications
0
67
0
Order By: Relevance
“…In the upper mesosphere, the photolysis of ozone (O 3 ) due to the solar radiation in the Hartley band (200-300 nm) acts as a complementary source of the atomic oxygen (O). The presence of atomic oxygen (O) in the mesosphere-lower thermosphere (MLT) region triggers a series of chemical reactions, and some among them are responCorrespondence to: N. Parihar (nparihar@iigs.iigm.res.in) sible for the nightglow phenomena (Brasseur and Solomon, 1984;Meriwether, 1989;Smith, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the upper mesosphere, the photolysis of ozone (O 3 ) due to the solar radiation in the Hartley band (200-300 nm) acts as a complementary source of the atomic oxygen (O). The presence of atomic oxygen (O) in the mesosphere-lower thermosphere (MLT) region triggers a series of chemical reactions, and some among them are responCorrespondence to: N. Parihar (nparihar@iigs.iigm.res.in) sible for the nightglow phenomena (Brasseur and Solomon, 1984;Meriwether, 1989;Smith, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[2] The nighttime O( 1 S) and OH airglow emissions in the mesosphere and lower thermosphere (MLT) originate from the recombination of atomic oxygen [e.g., reviews by McDade and Llewellyn, 1986;McDade et al, 1987;Meriwether, 1989]. Atomic oxygen is produced through the photo-dissociation of molecular oxygen in the thermosphere, and its global distribution in the MLT region is mainly controlled by dynamical transport processes [e.g., Garcia and Solomon, 1985;Brasseur and Solomon, 1986].…”
Section: Introductionmentioning
confidence: 99%
“…In his review of the terrestrial OH airglow, Meriwether (1989) concluded that, on Earth, reaction (2) is a negligible source of excited OH compared to the Bates-Nicolet mechanism…”
Section: Introductionmentioning
confidence: 99%